Physical Education Forms Students' Ethics, Morals, And Character - Abd. Patta; Muh Adnan Hudain; Ramli Ramli; Andi Ridwan; Yasriuddin Yasriuddin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. Physical education is an educational process that aims to promote the overall development of an individual by making them physically, mentally, and socially fit. It involves various physical activities like running, jumping, and playing sports that contribute to the overall physical fitness of an individual. Along with physical fitness, it also helps in developing mental strength, cognitive abilities, and social skills, which are essential for a healthy and happy life. The research aims to examine the role of physical education in developing ethics, morals, and character in students at SMPN 7 Selayar Islands. It will analyze how physical education can help students inculcate values such as discipline, teamwork, perseverance, and sportsmanship, which are essential for a successful and fulfilling life. The study will also explore how physical education can help students develop a positive attitude toward life, which will enable them to cope with challenges and overcome obstacles in their personal and professional lives. Materials and Methods. This research used a qualitative descriptive approach with five grade 7 students from Selayar Islands Middle School. Data was collected through observation, interviews, and documentation, and analyzed using data collection, display, condensation, and conclusion-drawing techniques. Results. Physical education has the potential to shape ethics, morals, and character positively. The various aspects of ethics, morals, and character indicators are well-integrated into the objectives of physical education. There are several elements present in physical education learning that can influence ethics, morals, and character formation. The results of questionnaires filled out by students have confirmed that physical education can shape students' ethics, morals, and character by 80%. Additionally, interviews were conducted to make in-depth observations and directly observe environmental conditions at SMPN 7 Selayar Islands. Conclusions. Physical education has the potential to shape the character of students at SMPN 7 in Selayar Islands. This can be observed from the students' bravery in participating in various sports, such as soccer and volleyball, despite the risk of injury. Despite injuries, students remain enthusiastic about physical education learning, and hobbies. This indicates that most students enjoy physical education and it has a positive impact on their character development.